Desafios Journal in its new challenge - Escobedo, Froilán (2019)
The University of Huanuco publishes its second issue of the Journal Challenges, with lines of research in the educational sciences, social sciences and humanities, touching to make a comment to arouse the interest of teachers and students and continue to promote the development of scientific research and making visible the scientific production. There is no doubt that this is a function that the university has been assuming; as well as that it will reach its goals precisely when the subjects that the student takes are articulated with the research that is developed here. The university is no longer only a transmitter of knowledge, where the source of information was the teacher; its role has become one of guidance, one that motivates the student to seek knowledge through research, because the university is a center for the production of new knowledge, new techniques, seeking social welfare (Terrazas and Silva, 2013).